Factors that influence the improvement of financial performance of Micro, Small and Medium Enterprises in Java Island - Surjadi, Merna; Simandjuntak, Johanes B.P.; Hakki, Tandry Whittleliang; Rosewita, Bella (Ranah Research : Journal of Multidisciplinary Research and Development, 2025)
The role of Micro, Small, and Medium Enterprises (MSMEs) as the economic pillar of a developing country. Indonesia is one of the countries that prioritizes MSMEs as its economic strength. The purpose of this study is to analyze the influence of Accounting Information Systems, Financial Literacy, and Accounting Management Strategies on improving the financial performance of MSMEs. This study used primary data collected by distributing questionnaires to MSMEs on the island of Java, including MSMEs in Jakarta, Bandung, and Surabaya. The sampling technique used purposive sampling, with 153 respondents from a total of 170 questionnaires distributed. Data were analyzed using multiple linear regression with SPSS. The results of this study are: (i) Accounting Information Systems and Financial Literacy have a significant and positive effect on the financial performance of MSMEs. Meanwhile, Accounting Management Strategies do not have a significant effect on the financial performance of MSMEs. This study has limitations because it only examined MSMEs located on the island of Java. It is hoped that future research will be conducted on other islands, such as Sulawesi or Kalimantan.